Redesign of Unmanned Surface Vessel (USV) Hull to Increase the Performance and to Support Naval Operations - Hendri Priyono; Sovian Aritong; Mahesa Akbar (Journal Research of Social Science, Economics, and Management, 2022)
The Indonesian Navy's current unmanned vessel is the first unmanned ship made by the Indonesian Navy's Research and Development Service. This vessel is not optimal, it is necessary to redesign the hull using the model simulation method with the assistance of Maxsurf software. By using this maxsurf software, it will be easier to analyze hydrodynamic performance, one of which is the vessel's resistance. The redesign shows the results that there is a reduction in ship resistance. By redesigning, the hull of the Indonesian Navy's unmanned vessel by using the model simulation method with the assistance of the Maxsurf software in analyzing hydrodynamic performance, we get the resistance value at maximum speed. Meanwhile, the power required by the ship is at maximum speed so that the speed shows an increase in maximum ship speed, thereby fulfilling the operational requirements and producing good maneuverability. Therefore, it can be concluded that the ship after being redesigned can be better.